Bottom-up approach to deciphering the targets of the ubiquitin-proteasome system in porcine sperm capacitation - Zigo, Michal; Netherton, Jacob; Zelenková, Natálie; Kerns, Karl; Kraus, Veronika; Postlerová, Pavla; Baker, Mark; Sutovsky, Peter (Scientific reports, 2024)
Capacitation is an essential post-testicular maturation event endowing spermatozoa with fertilizing capacity within the female reproductive tract, significant for fertility, reproductive health, and contraception. By using a human-relevant large animal model, the domestic boar, this study focuses on furthering our understanding of the involvement of the ubiquitin-proteasome system (UPS) in sperm capacitation. The UPS is a universal, evolutionarily conserved, cellular proteome-wide degradation and recycling machinery, that has been shown to play a significant role in reproduction during the past two decades. Herein, we have used a bottom-up proteomic approach to (i) monitor the capacitation-related changes in the sperm protein levels, and (ii) identify the targets of UPS regulation during sperm capacitation. Spermatozoa were capacitated under proteasomal activity-permissive and inhibiting conditions and extracted sperm proteins were subjected to high-resolution mass spectrometry. We report that 401 individual proteins differed at least two-fold in abundance (P < 0.05) after in vitro capacitation (IVC) and 13 proteins were found significantly different (P < 0.05) between capacitated spermatozoa with proteasomal inhibition compared to the vehicle control. These proteins were associated with biological processes including sperm capacitation, sperm motility, metabolism, binding to zona pellucida, and proteasome-mediated catabolism. Changes in RAB2A, CFAP161, and TTR during IVC were phenotyped by immunocytochemistry, image-based flow cytometry, and Western blotting. We conclude that (i) the sperm proteome is subjected to extensive remodeling during sperm capacitation, and (ii) the UPS has a narrow range of distinct protein substrates during capacitation. This knowledge highlights the importance of the UPS in sperm capacitation and offers opportunities to identify novel pharmacological targets to modulate sperm fertilizing ability for the benefit of human reproductive health, assisted reproductive therapy, and contraception, as well as reproductive management in food animal agriculture.
Keywords: Sperm capacitation; proteom; Ubiquitin-proteasome system; spermie; Proteomics; Sperm proteomics; ubikvitin; Sperm Capacitation; Pig; zvířata; proteomika; Swine; proteasomový endopeptidasový komplex; Proteasome Endopeptidase Complex; Male; Spermatozoa; Proteome; Animals; kapacitace spermií; mužské pohlaví; prasata; Ubiquitin